Health Promotion To Increase Exclusive Breastfeeding Coverage - cucu herawati; Reynalda Pooja Lestari; Iin Kristanti; Nuniek Tri Wahyuni; Uun Kurniasih; Healthy Seventina Sirait; Herlinawati; Muslimin; Rokhmatul Hikhmat (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The PHBS indicator shows that Optimizing breast milk is very important For the continuity of life generation next because That is important for Mothers To provide breast milk. Scope babies who are exclusively breastfed are Still low below the target of 100%. Low knowledge is one of the factors achievement of exclusive breastfeeding Still Far below target. The purpose of service to this Society is To give intervention promotion health in frame effort to increase the scope of exclusive breastfeeding. Implementation activity PkM This May 10-25 2024. The target intervention is for 16 breastfeeding mothers. Data collection techniques include interviews, observations, and studies documentation Stages intervention First do observations and stages second do counselling with Target breastfeeding mothers. Results of activities PkM found it based on priority problem health becomes priority problem that is exclusive breastfeeding that is amounting to 43.13% of the target of 100%. So activities intervention during PkM giving counselling and practising massage oxytocin to facilitate breast milk target 16 mothers breast-feed. The conclusion from results PkM This has given intervention counselling and practice massage oxytocin against 16 mothers breast-feed. The public health centre can increase counselling regarding exclusive breastfeeding and increase Work The same to improve achieving exclusive breastfeeding.